A QUAD CMOS GATES CHECKING METHOD - Tyurin, Sergey F. (International Journal of Computing, 2019)
The so-called Fault-Tolerant Systems (FTS) use the structural, temporal, functional, or information redundancy for the achievement of the high reliability. For example, Radiation Hardened by Design (RHBD) Systems are Fault-Tolerant Systems. A Passive FTS, due to a very large structural redundancy (Modular Redundancy), produces faults masking. The Triple Modular Redundancy (TMR) Method has more than 300% redundancy. The Quad Redundancy (QR) Method boasts more than 400% redundancy. The CMOS transistors QR (transistor-level redundancy) is the most effective QR. In this case, no voting element is needed. However, this significantly increases the time delay. In addition, it is necessary to ensure compliance with the Mead-Conway restrictions. QR, in contrast to TMR, raises the problem of checking the redundant structure. The author proposes a QR Checking Method based on a selection of substrates of the CMOS transistors. The power lines of the transistor substrates are separated, which ensures the disconnection of part of the reserve. A simulation confirms the feasibility of the proposed method.